Uji Diagnostik Genexpert Mtb/Rif Di Rumah Sakit Umum Pusat Haji Adam Malik Medan - Elva Susanty; Zainuddin Amir; Parluhutan Siagian; Rina Yunita; Putri Chairani Eyanoer (Universitas Negeri Medan, 2015)
Background: Cases of multidrug resistant tuberculosis (MDR TB) is increasing in number in the world and requires early detection to prevent further transmission. GeneXpert MTB/RIF is a tool that can be used for detection of rifampicin resistance, as a surrogate marker for MDR TB. This study aims to assess the sensitivity and specificity of the GeneXpert MTB/RIF in diagnosis of MDR TB. Methods: diagnostic test study was conducted at a poly MDR TB General Hospital Haji Adam Malik Medan. The subjects were all suspected MDR TB who had results positive GeneXpert MTB/ RIF with sensitive rifampin or resistant rifampin and had a drug sensitivity test results with the proportion method Lowenstein Jensen medium. Data retrieved from the medical records, between January until December 2013. Results: founded 64 samples that had results of GeneXpert MTB/RIF test positive and had the results of drug sensitivity, 87.5% of rifampin-resistant samples were also resistant to isoniazid. The GeneXpert MTB/RIF examination showed the sensitivity of 92.86% and the specificitu of 59.09%. Conclusion: GeneXpert MTB/ RIF has a high sensitivity for diagnosing MDR TB compared the gold standard drug sensitivity testing proportion method on Lowenstein Jensen medium. This study recommends the GeneXpert MTB/RIF be used for MDR TB screening tool. Keywords: GeneXpert MTB/RIF, multidrug resistant tuberculosis, drug susceptibility test, Lowenstein Jensen medium